1996
DOI: 10.1007/bf00055423
|View full text |Cite
|
Sign up to set email alerts
|

Coffee shade with Mimosa scabrella Benth. for frost protection in southern Brazil

Abstract: Damage by radiative frosts is a major limiting factor for coffee cultivation in southern Brazil (south of 20 ° S latitude). The use of Mimosa scabrella (bracatinga) as a shade tree, to modify the local energy balance and thus prevent damage to the coffee plants, has been evaluated from 1986 to 1994. The study was carried out near Londrina, Parana State (23023 ' S, 51°11' W). During the experimental period, several radiative frosts with intensity ranging from moderate to very severe occurred at the site, Minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
22

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 6 publications
3
30
0
22
Order By: Relevance
“…These papers describe the arborization in a qualitative manner about the type of the tree utilized, crop density. However few papers are found in literature that characterize the microclimate quantitatively such as in a coffee and dwarf coconut or Prata Banana systems in Mococa, Brazil (PEZZOPANE et al, 2003;2007), in an arborizated systems in Colômbia (FARFAN-VALENCIA et al, 2003), in an agroflorestal system in Mexico (BARRADAS and FANJUL, 1986) and in an arborizated system with 'bracatinga' in Londrina, Paraná state, Brazil (CARAMORI et al, 1996). These works showed that the microclimate is strongly influenced by wind, soil type, water deficit vapor, temperature and solar radiation and those elements are dependent to the climate, the species utilized for arborization and the crop density.…”
Section: Agronomic Technologies For Mitigation and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…These papers describe the arborization in a qualitative manner about the type of the tree utilized, crop density. However few papers are found in literature that characterize the microclimate quantitatively such as in a coffee and dwarf coconut or Prata Banana systems in Mococa, Brazil (PEZZOPANE et al, 2003;2007), in an arborizated systems in Colômbia (FARFAN-VALENCIA et al, 2003), in an agroflorestal system in Mexico (BARRADAS and FANJUL, 1986) and in an arborizated system with 'bracatinga' in Londrina, Paraná state, Brazil (CARAMORI et al, 1996). These works showed that the microclimate is strongly influenced by wind, soil type, water deficit vapor, temperature and solar radiation and those elements are dependent to the climate, the species utilized for arborization and the crop density.…”
Section: Agronomic Technologies For Mitigation and Adaptationmentioning
confidence: 99%
“…Shading has been adopted to avoid large reductions in night temperatures at high elevations, as in Kenya (CARR, 2001), or at high latitudes, as in Parana State (23-24°S), Southern Brazil (CARAMORI et al, 2003) in order to reduce frost damage.…”
Section: Agronomic Technologies For Mitigation and Adaptationmentioning
confidence: 99%
“…No ponto 1 do sistema consorciado, como esperado, ocorreram menores valores absolutos, devido à menor perda energética proporcionada por trocas radiativas com as folhas de bananeira. CARAMORI et al (1996), assim como BRENNER (1996) também verificaram o efeito protetor de árvores utilizadas em cultivos arborizados.…”
Section: Analisando Os Dados Médios Do Três Sensores Do S I S T E M Aunclassified
“…Dentre as principais culturas produzidas em agrossistemas arborizados ou consorciados, o café é das mais estudadas (BARRADAS e FANJUL, 1986;BEER, 1987;CARAMORI et al, 1996). Para a c u l t u r a d o c a f e e i r o , o u s o d e s i s t e m a s consorciados visa minimizar a exposição das plantas a riscos climáticos como geadas, excessos de radiação solar, temperaturas elevadas e ventos excessivos.…”
Section: Introductionunclassified
“…Frost damages may also vary with cultivar characteristics such as height, vigor, and production of coffee beans on the year with frost Sera, 1978, 1979;Siqueira et al, 1983;Androcioli Filho et al, 1986), plant nutrition (Chaves and Manetti Filho, 1990), and with the level of shade of the coffee plantation (Caramori et al, 1996).…”
Section: Introductionmentioning
confidence: 99%